ANALISIS KERUSAKAN MESIN GEMINI FICEP G25 SP CNC MENGUNAKAN METODE FAILURE MODE EFFECT ANALYSIS (FMEA) - Habibberi Agil Rabani; Iman Dirja; Najmudin Fauji (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2022)
The rapid development of the manufacturing industry requires companies to always produce high quality and fully functional products. However, when the production process does not always run, there should be problems encountered, such as the machine factor which often breaks down and even shuts down completely, causing production disruption. One of the important factors in the successful implementation of Failure Mode Effect Analysis (FMEA) is to interpret before, the process takes place and not after it occurs. To support the implementation of Failure Mode Effect Analysis in the field of maintenance, an effort is needed to improve the state of the equipment. So, in this study, this method will be applied to the maintenance of the Gemini Ficep G25 CNC machine. The result can be assumed to be the primary problem in damage. The trouble that must be prioritized first are the plasma doesn’t run, the force on the engine drive does not move, the dust collector does not work and the internal and external coolants water don’t come out.